Konkurenceschopnost v pojetí globalizace - Vrtěnová, Lucie; Sobotka, Martin (Univerzita Pardubice, 2009)
The paper deals with mutual relations between competitiveness and globalization process. The impacts of globalization not only on competitiveness of businesses but also regions and states are characterized in this article. As the globalization and the competitiveness are mutually influencing phenomena, the opposed impact of an effort concerning increasing microeconomic and macroeconomic competitiveness on world's economic development is searched in this article as well.
Keywords: Competitiveness; European Union; Globalization; international trade